2009
DOI: 10.1094/mpmi-22-2-0190
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling in Hybrid Poplar Following Interactions with Melampsora Rust Fungi

Abstract: In natural conditions, plants are subjected to a combination of biotic stresses and often have to cope with simultaneous pathogen infections. In this report, we aim to understand the global transcriptional response of hybrid poplar NM6 (Populus nigra x P. maximowiczii) to infection by two biotrophic Melampsora fungi, Melampsora larici-populina and M. medusae f. sp. deltoidae. These pathogens triggered different responses after inoculation of poplar leaves. Transcript profiling using the GeneChip Poplar Genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 58 publications
8
86
1
2
Order By: Relevance
“…Despite this, the trends we observed in gene expression are informative. Supporting previous work on quantitative resistance in Populus (Miranda et al 2007, Azaiez et al 2009), several defense-related genes were strongly up regulated (.5 fold) following pathogen inoculation (e.g., Ptgluc, PtATOSM34, PtGSTU25, PtWRKY51, PtCAD9) (Table 1). In particular, the expression of PtATOSM34, a gene coding for a defense protein, was more than 38 times greater in plants inoculated with Drepanopeziza than in control plants (Table 1).…”
Section: Endophyte Effects On Gene Expressionsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite this, the trends we observed in gene expression are informative. Supporting previous work on quantitative resistance in Populus (Miranda et al 2007, Azaiez et al 2009), several defense-related genes were strongly up regulated (.5 fold) following pathogen inoculation (e.g., Ptgluc, PtATOSM34, PtGSTU25, PtWRKY51, PtCAD9) (Table 1). In particular, the expression of PtATOSM34, a gene coding for a defense protein, was more than 38 times greater in plants inoculated with Drepanopeziza than in control plants (Table 1).…”
Section: Endophyte Effects On Gene Expressionsupporting
confidence: 83%
“…Two genes of particular interest-PtATOSM34 and PtGlyHy17-code for defense-related proteins. A previous study found all fifteen genes were up-regulated in response to inoculation with the rust pathogen Melampsora (Azaiez et al 2009). …”
Section: Gene Expression Analysismentioning
confidence: 94%
“…2B). Mmd rust is known to elicit a strong defense response in this hybrid poplar (Azaiez et al, 2009;Boyle et al, 2010), as suggested here by the increase in PtiPR1 transcript in the infected leaves (Fig. 2B).…”
Section: Isolation Of Ptizfp1: a Mapk-interacting Partnersupporting
confidence: 65%
“…Infection of NM6 poplar with Mmd rust results in host-specific partial resistance that still allows a certain extent of fungal growth. NM6 hybrids are thus considered susceptible, and the defense response (quantitative resistance) associated with this host-microbe interaction was described elsewhere (Azaiez et al, 2009;Boyle et al, 2010). Among the peptides selected for their potential interaction with PtiMPK3-1, we identified a truncated cDNA coding for the last 104 amino acids of a putative TF.…”
Section: Isolation Of Ptizfp1: a Mapk-interacting Partnermentioning
confidence: 99%
See 1 more Smart Citation